Customer satisfaction and brand loyalty for the apple brand in batam city: understanding the influential factors - Delvin Lim; Augustino Sanduo; Jason Andrian; Jeffrey Andrian; Vincentius Junior Samudra (Trigin Publisher, 2023)
Customer satisfaction and brand loyalty are key determinants of business success in today’s competitive market. With the rapid growth of technology brands, such as Apple, understanding the factors that influence customer satisfaction and brand loyalty is essential. The purpose of this study aims to explore those influential factors that contribute to customer satisfaction and brand loyalty towards Apple brand in Batam city. The research methodology employed a quantitative approach, distributed forms to a sample of 404 respondents. The data collected was subsequently analyzed and processed using SEM with SPSS AMOS. The findings of this study indicate that all independent variables exhibit positive effects on customer satisfaction variable. Furthermore, customer satisfaction demonstrates a positive and significant impact on brand loyalty. These outcomes are expected to contribute significantly to both official and unofficial stores of apple products in Batam city in dealing with their marketing strategies.